From Theory to Praxis: Humanizing Pedagogy in EFL Practicum - Chaleila, Wisam Abughosh (Journal of Posthumanism, 2025)
Efforts to incorporate academic content into practicum for pre-service teachers (PSTs) aim to enhance learning but face implementation challenges, reflecting global concerns about teacher preparedness and professional identity. This study examines the perceptions of 19 English PSTs in Israel enrolled in the “From Theory to Praxis” (FTTP) program, a newly tailored practicum model integrating academic institutions with school-based teaching. Using a narrative qualitative approach, the study explored personal and social dynamics shaping pedagogical development (Philipsen et al., 2019). Findings revealed that supervised, hands-on experience in real-world settings supported the development of pedagogical identity and humanistic teaching, emphasizing empathy, immediacy, engagement, and student well-being. Reflecting on their personal and professional growth, PSTs viewed FTTP as a transformative platform for teacher development. The study highlights the importance of collaboration between schools and training institutions and offers insights for bridging the theory-practice gap. It concludes with recommendations for refining global teacher education policy.